Keefektifan Layanan Konseling Kelompok untuk Meningkatkan Kepercayaan Diri Siswa - Nurul Alifah; Oktavia Utami Ramadhani; Annisa Rahman; Shinta Nurhaliza; Ratna Sari Dewi (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
Self-confidence is a crucial aspect of student development and academic success. However, many students still struggle with low self-confidence. This article reviews the effectiveness of group counseling through a literature review of 22 journals (2013–2025). Findings show that group counseling effectively enhances self-confidence across various educational levels. Techniques used include REBT, bibliocounseling, self-instruction, and role play. Success also depends on the stages of implementation. Group counseling provides a reflective and supportive space, making it a suitable intervention strategy in guidance and counseling programs.